2020
DOI: 10.1186/s12964-019-0500-x
|View full text |Cite
|
Sign up to set email alerts
|

Sialidase NEU1 suppresses progression of human bladder cancer cells by inhibiting fibronectin-integrin α5β1 interaction and Akt signaling pathway

Abstract: Background: Sialic acids are widely distributed in animal tissues, and aberrantly expressed in a variety of cancer types. High expression of sialic acid contributes to tumor aggressiveness by promoting cell proliferation, migration, angiogenesis, and metastasis. Sialidases are responsible for removal of sialic acids from glycoproteins and glycolipids. Methods: N-glycomics of bladder cancer cells were detected by MALDI-TOF mass spectrometry. Sialic acid modification in bladder cancer tissue was determined by le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…Sialic acids have been found to mediate a large number of glycoprotein interactions, including adhesion receptors such as the β1-integrin, a receptor for FN (Johansson et al, 1997;Schultz et al, 2012;Xie et al, 2021). In cancers that overexpress NEU1 the enzyme has been found to act as a negative regulator of migration through disruption of β1-and β4-integrin interactions (Uemura et al, 2009;Zhou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sialic acids have been found to mediate a large number of glycoprotein interactions, including adhesion receptors such as the β1-integrin, a receptor for FN (Johansson et al, 1997;Schultz et al, 2012;Xie et al, 2021). In cancers that overexpress NEU1 the enzyme has been found to act as a negative regulator of migration through disruption of β1-and β4-integrin interactions (Uemura et al, 2009;Zhou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Zhou et al. ( 69 ) recently reported that NEU1 overexpression in human bladder cancer cells diminished cell proliferation and enhanced apoptosis, in part, through disruption of PI3K-Akt signaling.
Figure 7 NEU1 disrupts the MUC1-CD/PI3K/Akt pathway: A proposed model.
…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous sialidase NEU1 resides in two subcellular compartments with distinct homeostatic functions; lysosomal NEU1 regulates cytosolic SIA levels by recycling sialoconjugates [ 75 ], whereas in the plasma membrane it initiates inflammatory cascades via desialylation of surface molecules such as ICAM-1 [ 76 ] and TLR4 [ 77 ]. NEU1-mediated SIA cleavage also inhibits Akt signaling downstream of integrin α5β1 [ 78 ] and the latter mediates proinflammatory NF-kB activation in response to OSS [ 79 ]. In the present study, NEU1 silencing enhanced SIA expression in cells exposed to USS but had little effect on SIA levels following exposure to OSS, likely due to the sustained deficit in SIA biosynthesis described above.…”
Section: Discussionmentioning
confidence: 99%